Analytic Hierarchy Process Based Prioritisation and Taxonomy of Success Factors for Scaling Agile Methods in Global Software Development. Issue 4 (1st August 2020) - Shameem, Mohammad; Khan, Arif Ali; Hasan, Md. Gulzarul; Akbar, Muhammad Azeem
Abstract : Global software development (GSD) organisations are currently adopting agile frameworks in order to efficiently develop a software product. The main objective of this study is to identify the success factors (SFs), which could possibly have a positive impact on scaling agile practices in a GSD environment and develop their taxonomy based on their prioritisation using the analytic hierarchy process (AHP) approach. This study is conducted in four stages: problem identification and goal of the study (1), identification of SFs and their categorisations (2), validation of the SFs using questionnaire survey (3), and application of AHP to prioritise the SFs and develop the taxonomy of the SFs and their respective categories (4). The results of this study indicated that 'technology' is the most significant category as compared to the other categories of the SFs. Similarly, rich technological infrastructure is identified as a most important factor. Based on the findings of this study, authors can conclude that the contribution of this study is not only limited to development of the taxonomy of the SFs, but also their proper prioritisation by introducing AHP approach, which assists software organisations to scale agile methods effectively in the GSD environment.